2010
DOI: 10.1186/1471-2105-11-324
|View full text |Cite
|
Sign up to set email alerts
|

Detecting lateral gene transfers by statistical reconciliation of phylogenetic forests

Abstract: BackgroundTo understand the evolutionary role of Lateral Gene Transfer (LGT), accurate methods are needed to identify transferred genes and infer their timing of acquisition. Phylogenetic methods are particularly promising for this purpose, but the reconciliation of a gene tree with a reference (species) tree is computationally hard. In addition, the application of these methods to real data raises the problem of sorting out real and artifactual phylogenetic conflict.ResultsWe present Prunier, a new method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 29 publications
0
74
0
Order By: Relevance
“…2 only the results for the root position that minimizes the LGT number; however, this means that the minimum LGT score can also provide information on the position of the root of the reference tree. In our previous simulations, we found that the true root was indeed characterized by the best LGT score (12). Thus, we looked whether the LGT score could discriminate among possible roots for each phylum by using a statistical test (Wilcoxon paired test, α = 5%) to compare the score of different roots.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 only the results for the root position that minimizes the LGT number; however, this means that the minimum LGT score can also provide information on the position of the root of the reference tree. In our previous simulations, we found that the true root was indeed characterized by the best LGT score (12). Thus, we looked whether the LGT score could discriminate among possible roots for each phylum by using a statistical test (Wilcoxon paired test, α = 5%) to compare the score of different roots.…”
Section: Resultsmentioning
confidence: 99%
“…We show that independent sets of gene families support a same species tree and that most branches (>90%) of a gene tree are compatible with a pattern of vertical inheritance. The parameter (branch support value) used here to detect LGT was chosen based on the results of previous simulations (12), which showed a best compromise for sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used PRUNIER (16) to estimate the number of transfers among 474 near universal single copy gene families from 36 cyanobacterial genomes. PRUNIER performs statistical reconciliation taking into account branch supports and is capable of recovering the number of transfers for single copy families given a threshold of statistical support.…”
mentioning
confidence: 99%
“…1). Most studies aimed at evaluating the role of gene transfer using phylogenetic approaches have tried to circumvent the problem of duplications and loss of genes by focusing on genes that are present in at most one copy in each genome (Beiko et al 2005;Than et al 2008;Abby et al 2010Abby et al , 2012Puigbò et al 2010). Only recently, new methods have been developed that can sort out the role of duplication, transfer, and loss in gene histories (Bansal et al 2012;Szölló´si et al , 2013bSjöstrand et al 2014).…”
Section: The Many Facets Of Horizontal Transfermentioning
confidence: 99%